Avaliação da inclusão de taninos na dieta ou do turno de pastejo como estratégias para melhorar o uso do nitrogênio alimentar em vacas leiteiras - Pozo, Claudio Antonio (2018)
The aim of this study was evaluate if including Acacia mearnsii tannin extract (TA) in the diet or managing the grazing schedule impacts on ingestive, digestive and productive response of dairy cows grazing ryegrass combined with total mixed ration (TMR). Nine lactating Holstein cows were arranged on a triplicate 3 x 3 Latin square design, conducted through three experimental periods of 22 d. The three treatments consisted of: morning grazing and afternoon TMR without TA (AM), morning grazing and afternoon TMR added with 15 g TA/kg of dry matter (DM) (AMt), and morning TMR without TA and afternoon grazing (PM). Treatments did not affect the DMI, but PM increased the percentage of pasture in the diet, and induced little changes on nutrients intake. The proportion of cows eating, ruminating or doing other activities through 16 h-observations was not affected by the treatments, however AM achieved high dry matter intake rate (DMIR) of TMR than PM. Also, AMt and PM increased the proportion of time spent eating TMR in 2 h relative to start of feeding. At grazing, the DMIR of pasture was similar for all treatments. In addition, cows in AM and AMt displayed a similar behavior pattern and showed two peaks of grazing, while the proportion of cows grazing in PM seems to be more stable than AM and AMt. Treatments did not affect the milk production or milk constituents yield. Dietary tannin tended to reduce the percentage of protein and casein in the milk, however did not impact on milk protein and casein production. Although, AMt induced little changes on milk FA, the most relevant FA in milk remain unchanged. In the same way, AM and PM present a similar profile of FA in the milk. Treatments did not affect the rumen fermentation parameters. No differences among treatments were detected in microbial protein flow to the duodenum, nor most of digestibility variables. The intake of N fractions and the excretion of N in milk and feces were similar between treatments. However, AMt and PM lowered the amount of N and N-urea excreted in urine. Although the excretion of total manure N was not affected by treatments, the urinary N to fecal N ratio were lower in both AMt and PM in comparison with AM. It is concluded that the inclusion of low amounts of TA in the TMR or grazing in the afternoon were both effective strategies to reduce the excretion of urinary N without impacting negatively on nutrient digestion nor performance of lactating dairy cows.